The Nature of Financial Innovation: A Post-Schumpeterian Analysis. Issue 3 (3rd July 2018) - Akdere, Çinla; Benli, Pelin
Abstract: Is it possible to apply a Schumpeterian notion of entrepreneurial innovation to the financial sphere? Joseph A. Schumpeter, arguing that innovation could only be proposed by entrepreneurs and take place predominantly in the real sector, seems to propose a foundation for a contemporaray analysis of financial innovations. There is a lack of specific emphasis on the evolution of financial innovations in Schumpeter's work. The purpose of the paper is to demonstrate that Schumpeter's analysis of entrepreneurial innovation, which takes place in the real economy, also proposes a theoretical account for understanding the dynamics of financial innovations. Our aim is to propose a comparative study between entrepreneurial innovations and financial innovations. Nevertheless, analyzing financial innovations in the framework of Schumpeter's economic theory doesn't mean to legitimize them all. This is also an investigation for diversifying financial innovations according to their impact on the real economy. We provide a basic foundation for a post-Schumpeterian description of the evolution of the capitalist system.